ANALISIS KEMAMPUAN PEMAHAMAN SISWA DALAM PEMBELAJARAN PAI MELALUI MEDIA AUDIO DAN VISUAL - Rahim , Muhammad Abdul (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This research examines the analysis of students' understanding abilities in PAI learning through audio and visual media. So the aim of this research is to determine the development and extent to which students grasp the understanding of PAI learning with the help of technology. This research uses descriptive qualitative research. using a phenomenological approach to try to make sense of an event and socializing with someone. This technique uses observation, interview and documentation data collection techniques. Based on the results of research found in the field, with the help of technology, students' interest and interest becomes high so that understanding of the material presented goes well. The increase in students' understanding ability increases with the achievement results of students who can pass the munaqosah exam and can carry out khataman and also during practice, one of which is the Hajj ritual.